Characterization of occlusal splint materials: CAD-CAM versus conventional resins. (December 2021) - Gibreel, Mona; Perea-Lowery, Leila; Vallittu, Pekka K.; Lassila, Lippo
Abstract: Aim: The aim of this in vitro study was to assess the mechanical properties of five commercially available subtractive computer-aided design and computer-aided manufacturing (CAD-CAM) milled splint materials, as well as to compare them with conventional heat-polymerized and autopolymerizing resins used in the construction of conventional splints. Material and methods: Five CAD-CAM milled (ProArt CAD Splint, Therapon Transpa, Temp Premium Flexible Transpa, Cast, and Aqua), one autopolymerizing (Palapress), and one heat-polymerized (Paladon 65) resin materials were evaluated. Flexural strength, E-modulus, Vickers hardness, fracture toughness, fracture work, water sorption, and water solubility were measured. Samples were evaluated after dry and water storage for 30 days at 37 °C. Data were collected and statistically analyzed. Results: Under both storage circumstances, the flexural strength values of Paladon 65, Therapon Transpa, Temp Premium Flexible Transpa, and Aqua were statistically non-significant ( P =0.055). The polycarbonate-based CAD-CAM material Temp Premium Flexible Transpa had the highest statistically significant values of the fracture toughness and fracture work ( P <0.001). Moreover, it exhibited the lowest percentages of water sorption and water solubility among the investigated materials ( P <0.001). All of the CAD-CAM materials exhibited dry elastic moduli greater than Palapress and lower than Paladon 65. One of the CAD-CAM materials, Cast, had the highest dry Vickers hardness value, which was non-significant when compared to Therapon Transpa ( P =0.762). Conclusion: CAD-CAM polycarbonate-based splint materials exhibit higher fracture toughness and fracture work as well as lower water sorption and solubility than polymethyl methacrylate-based ones. The mechanical characteristics of the assessed CAD-CAM milled splint materials were not typically superior to those of the conventional heat-polymerized resin. However, some of them outperformed the autopolymerizing acrylic resin in terms of flexural strength, surface microhardness, water sorption, and water solubility.